Accuracy of Nodal Positivity in Inadequate Lymphadenectomy in Pancreaticoduodenectomy for Pancreatic Ductal Adenocarcinoma: A Population Study Using the US SEER Database - Wang, Weishen; Shen, Ziyun; Shi, Yusheng; Zou, Siyi; Fu, Ningzhen; Jiang, Yu; Xu, Zhiwei; Chen, Hao; Deng, Xiaxing; Shen, Baiyong (Frontiers in Oncology, 2019)
Objectives: The optimal number of the examined lymph nodes (ELNs) in pancreaticoduodenectomy for pancreatic ductal adenocarcinoma was widely discussed. However, we did not have the information on the accuracy of the nodal positivity for the patients with inadequate lymphadenectomy. The propose of our study is try to determine the probability that the number of positive nodes reported is accurate for patients with 1–3 positive nodes, moreover, the probability that 4 or more nodes could be positive based on tumor size and number of nodes examined. Methods: Data on patients undergoing pancreaticoduodenectomy for resectable pancreatic ductal adenocarcinoma diagnosed during 2004-2013 were obtained form US Surveillance, Epidemiology and End Results (SEER) registries. A appropriate mathematical model was used. Results: Among 9945 patients, 55.6% were undergone an inadequate lymphadenectomy. 18.5% was T1 stage, 60.8% was T2 stage and 20.7% was T3 stage. The accuracy of the number of observed positive nodes increased as the number of ELNs increased and the tumor size decreased. To rule out the possibility of N2 stage, the minimal number of ELNs was 13 for the patients with 1 observed positive lymph node and 14 for the patients with 2. Conclusion: Inadequate lymphadenectomy could result in underestimation of the N stage, which would have adverse impact on the overall survival, the recurrence and even the postoperative treatment of the patients. This model combined by the observed positive lymph nodes, the ELNs and the tumor sizes could provide the accuracy of the nodal positivity of these patients for the clinicians.